PEMBUATAN ALAT PENDETEKSI ARAH MATA ANGIN MENGGUNAKAN SENSOR ROTARI BERBASIS MIKROKONTROLLER ATMEGA 16 - Oke Hermanto AP; Toibah Umi Kalsum; Hermawansyah Hermawansyah (Jurnal Media Infotama, 2014)
The problems of the research are to detect the direction of the wind using a rotary sensor based microcontroller. The software used includes operating systems, programming languages and software for data processing. The operating sys-tem is Microsoft Windows XP3 is used as the operating system. The programming language used is Basic Programming Language - Bascom AVR, Visual Basic 6.0. The test is done to test the detector's cardinal directions with laying outdoors and running properly in accordance with the design is that it can determine the direction of the wind.Keywords : The wind, sensor and microcontroller.